Multivariate analysis in chilli (Capsicum annum L.) - DOBHAL, G PANDEY, V K (Journal of Spices and Aromatic Crops, 1993)
Thirty genotypes of chilli (Capsicum annum) were studied for genetic divergence for eight characters utilizing Mahalanobis D2 statistics. The genotypes were grouped into seven clusters. The genotype GP-65(A) was quite different and formed cluster VII. Variability in this material was limited and was mainly due to a few extreme types. The genotype(s) in clusters II, V and VII had the highest dry yield per plant and higher values for fruits per plant, fruit length and days to flower and could be utilized in breeding programmes.